PENGEMBANGAN MEDIA VIDEO ANIMASI MENGGUNAKAN DORATOON PADA TEMA 8 PRAJA MUDA KARANA SUBTEMA 2 AKU ANAK MANDIRI - Ratu Gumy, Putri; Kurniasih, Surti; Resyi A. Gani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Development of animated videos using Doratoon on theme 8 praja muda karana subtheme 2 I am an independent child at SDN Sukamakmur, Bogor Regency. The problem in this study is that the learning media used by teachers still use printed media in the form of books. The purpose of this research is to develop animated video media and find out the students' responses to animated video media using Doratoon. The model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). Data analysis techniques include qualitative techniques and quantitative techniques. The results of research and development in the form of a media expert validation test of 90%, language experts of 100%, and material experts of 89% mean that the product is very feasible to use. The student response questionnaire obtained a percentage of 87% with very good criteria. Therefore, the development of animated video media using Doratoon is declared feasible when learning.